A Powerful One‐Step Puffing Carbonization Method for Construction of Versatile Carbon Composites with High‐Efficiency Energy Storage. Issue 40 (23rd August 2021) - Shen, Shenghui; Huang, Lei; Tong, Xili; Zhou, Rongfan; Zhong, Yu; Xiong, Qinqin; Zhang, Lingjie; Wang, Xiuli; Xia, Xinhui; Tu, Jiangping
Abstract: Carbon materials play a critical role in the advancement of electrochemical energy storage and conversion. Currently, it is still a great challenge to fabricate versatile carbon‐based composites with controlled morphology, adjustable dimension, and tunable composition by a one‐step synthesis process. In this work, a powerful one‐step maltose‐based puffing carbonization technology is reported to construct multiscale carbon‐based composites on large scale. A quantity of composite examples (e.g., carbon/metal oxides, carbon/metal nitrides, carbon/metal carbides, carbon/metal sulfides, carbon/metals, metal/semiconductors, carbon/carbons) are prepared and demonstrated with required properties. These well‐designed composites show advantages of large porosity, hierarchical porous structure, high conductivity, tunable components, and proportion. The formation mechanism of versatile carbon composites is attributed to the puffing‐carbonization of maltose plus in situ carbothermal reaction between maltose and precursors. As a representative example, Li2 S is in situ implanted into a hierarchical porous cross‐linked puffed carbon (CPC) matrix to verify its application in lithium–sulfur batteries. The designed S‐doped CPC/Li2 S cathode shows superior electrochemical performance with higher rate capacity (621 mAh g –1 at 2 C), smaller polarization and enhanced long‐term cycles as compared to other counterparts. The research provides a general way for the construction of multifunctional component‐adjustable carbon composites for advanced energy storage and conversion. Abstract : A powerful one‐step puffing carbonization technology is proposed to synthesize versatile multiscale carbon‐based composites (e.g. carbon/metal oxides, carbon/metal carbides, carbon/metal sulfides, carbon/metals, metal/semiconductors, etc.) with controlled morphology, adjustable dimensions and tunable composition on a large scale. As a representative example, a sulfur‐doped cross‐linked puffed carbon (SCPC)/Li2 S electrode shows extraordinary performance with superior rate capability and ultrastable cycling life.